Exploring fine compounds and biomass potential in Cabralea canjerana and Cordia americana wood - Santos, Mateus Berwaldt; Moreira, Eduardo Ceretta; Leitzke, Amanda Fonseca; Ramos, Maurício Alves; dos Santos, Patricia Soares Bilhalva; Fuentes, Silvia Helena; Gatto, Darci Alberto (Frontiers in Chemical Engineering, 2025)
Cabralea canjerana and Cordia americana, two Brazilian tree species found across various states, serve a range of applications from sawmill products to folk medicine. The extractives, non-structural wood components, are utilized for diverse purposes, including natural dyes, preservatives, and medicinal products. After a comprehensive search of the literature, no publications were found characterizing the chemical composition of C. canjerana and C. americana wood. This increases the need to research these species and learn more about their potential. The vast diversity of Brazil’s tree species sometimes complicates the selection process for extraction purposes, highlighting the importance of anatomical wood identification. This study evaluates the presence of fine molecules with important biological activity or industrial value in the wood extractives of C. canjerana and C. americana, proposing potential uses for the extracted lignocellulosic biomass and providing anatomical identification support for these species. Characterization methods of the wood included analysis of ash, hemicellulose, cellulose, and lignin content. Extraction techniques employed ethanol, ethanol-toluene, hot water, and 1% soda, followed by gas chromatography-mass spectrometry (GC-MS) for chemical analysis. Anatomical characteristics were determined using histological slides. The results show that Cordia americana displayed a 53.61% holocellulose content in relation to the dry mass, suitable for paper production, while Cabralea canjerana, with a 55.92% content, was deemed even more appropriate. GC-MS analysis identified several significant molecules in the extractives, including Phenol, 2,4-bis(1-phenylethyl), which is potentially effective in breast cancer drug development, and Gestrinone, a possible treatment for endometriosis. The anatomical examination of the C. canjerana and C. americana samples confirmed their species identity, aligning with the study’s objectives.